DESAIN DIDAKTIS VOLUME KUBUS DAN BALOK UNTUK MENINGKATKAN KEMAMPUAN NUMERASI SISWA KELAS IV - Lestari Handayani, Tri; Abdul Muiz Lidinillah, Dindin; Fitri Apriani, Ika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop a didactical design on the material of cube and rectangular prism volume to improve the numeracy skills of fourth-grade students at SDN Bingkeng 02. This research employs a qualitative approach using Didactical Design Research (DDR) method. The research subjects are 17 fourth-grade students of SDN Bingkeng 02. Data were collected through participatory observation, in-depth interviews, diagnostic tests, and documentation. The results indicate that the didactical design developed based on the analysis of students' learning obstacles was able to reduce learning barriers and improve students' numeracy skills, particularly in the aspects of conceptual understanding of volume, formula application, and contextual problem-solving related to cubes and rectangular prisms. The developed didactical design includes didactical situations, didactical-pedagogical anticipations, and systematic predictions of student responses. The implications of this research are expected to serve as a reference for teachers in designing responsive mathematics learning that meets students' needs.